Animal Abuse in the View of Islamic Criminal Law - Farizi, Salman (PT. Riset Press International, 2023)
Islam as the majority religion in Indonesia teaches us to be a mercy to the universe, including taking care of animals on earth. However, Indonesia is the country with the largest number of downloaders of animal abuse content in the world. Therefore, the purpose of this study is to analyze these problems from the perspective of jurisprudence. The research method used is normative legal research with a statutory approach and analysis of Islamic legal theories. The results of this study indicate that the crime of mistreatment of animals in Indonesia is regulated in the Criminal Code (KUHP) Article 302 and Article 540, as well as Law Number 18 of 2009 as amended by Law Number 41 of 2014 concerning Animal Husbandry and Health. Animal abuse in jinayah fiqh is included in the ta'zir finger, in which the level and punishment are determined by the government ( ulil amri ).